Rain induced scintillation measurement on satellite link in tropical climate - Islam, Md. Rafiqul; Al-Khateeb, Khalid A. Saeed; Mohd. Isa, Farah Nadia; Dao, Hassan; Mohd. Salleh, Hamzah; Ghazali, M.A. M. (2014)
Attenuation time series were collected to study the rain induced scintillation during September 2011 – August 2012 from MEASAT3 satellite operating at Ku-band. In this paper, scintillation statistics are analyzed in rainy condition extracted manually from 188 rainy events. The scintillation distributions are represented scintillation intensity and amplitude by monthly, seasonal, worst-month and annual distributions. Probability density function (PDF) of scintillation intensity correspondingly agrees to Generalize Extreme Value (GEV) fit. In addition, model validation to the measured data is also provided.